Addressing Inequality in Budgeting Lessons from Recent Country Experience (OECD Publishing, 2024)
In many countries, public expenditure, including transfers, plays a major role in reducing income inequality. The report reviews the various ways that budgeting can be used to this end. A first includes taking a broad approach to results-based budgeting, taking social and distributional goals into consideration. A second relies on integrating distributional impact analysis directly into the budget process. The report discusses the concrete experience of eight OECD countries in this area, analysing how they are integrating distributional impact assessment in spending and budgeting decisions. Finally, it discusses the tools, frameworks and data that are needed to take distributional considerations into account as part of evidence-informed policy making